Successful management of donor-acquired fat embolism after lung transplantation. (14th February 2021) - Glorion, Matthieu; Sarsam, Matthieu; de Wolf, Julien; Sage, Edouard
Abstract: Fat embolism is a serious complication in patients with multiple traumatic injuries. It is often asymptomatic during the first hours of resuscitation, thus remains underdiagnosed in patients who progress to brain death. Lung transplantation issued from such grafts can lead to severe lung primary graft dysfunction, the management of which is deemed difficult. Herein, we report a successful management of donor-acquired fat embolism syndrome after lung transplant in a 22 years old woman for cystic fibrosis. Fat embolism was suspected because of the donor's traumatic injuries and confirmed by histopathological analysis. An immediate postoperative primary graft dysfunction was successfully managed with veno-arterial extracorporeal membrane oxygenation. The patient is alive 31 months after surgery.